On the international flow of plant genetic resources: Forecasting the impacts of an evolving legal framework on CGIAR genebanks. - Gotor, Elisabetta; Caracciolo, Francesco; Scafetti, Flavia (Bioversity International, 2019)
Recognizing the linkages between the ITPGRFA and the CGIAR operations within the MLS, the present study aims at understanding the implications that the SMTA reform will have on the CG genebanks. To achieve its objective, the study starts by retracing the historical evolution of the legal framework guiding the international exchange of PGR. Then, it outlines the main features of the MLS reform processes currently being negotiated and identifies major challenges and sources of future uncertainties. By isolating those components relevant for CGIAR, the study constructs the different scenarios that might occur, and forecast the likelihood of different impacts and consequences for CG genebanks.